Investigating the Effectiveness of Different Disinfectants in Removing the Coronavirus: A Review Study - Maryam Nouri Goushki; Majid Nozari (Muhandisī-i Bihdāsht-i Muḥīṭ, 2022)
Viral infections have caused various diseases and deaths worldwide. In recent years, the emergence of the coronavirus has caused severe respiratory tract infections and led to a global concern. This study aims to investigate the effectiveness of various disinfectants that have been used to control the coronavirus. Methods: The present study is a systematic review. Data was collected through searching articles in databases, including Springer, Google Scholar, Prospero, Cochrane, ISI, Scopus, Embase, PubMed, and DOAJ. After searching and collecting articles related to the goal, the articles were categorized. The required data were extracted and finally analyzed. Results: The review of various studies showed that the coronavirus could remain infectious on inanimate surfaces for 9 days. Also, some studies have reported the presence of the coronavirus in feces. The articles' findings revealed that the coronavirus infectivity on surfaces is reduced by 62-71% ethanol, 0.5% hydrogen peroxide, and 0.1% sodium hypochlorite at 1 min. Also, the coronavirus in septic tank wastewater is inactivated by 800 to 6700 g/m3 of sodium hypochlorite at a contact time of 1.5 hours. In addition, the coronavirus in air aerosols is reduced under UVC radiation by 5 logs at 4 to 9 seconds. Conclusion: Effective drugs and vaccines have been made for the covid-19 disease to date. However, due to the unexpected mutations of the coronavirus, identifying disinfectants effective in removing different strains of the coronavirus from different surfaces and environments can be a suitable measure to prevent the spread of the covid-19 disease.